EFFECTIVE WAYS OF TEACHING FORIEGN LANGUAGES OF STUDENTS WITH BEGINNER LEVEL - Normuradova Nasiba Saydullayevna (Journal of new century innovations, 2023)
Abstract: This article describes the learning language that introduce with different people’s tradition, their culture, religious and physiological inner-world and the teacher’s task about the psychological atmosphere in class; importance in reaching the desirable effect of the activity.